Study on the Influence of Floating Sun Gear on the Dynamic Characteristic of Planetary Gear Transmission System - Zhanli Yang; Yinghui Liu; Jirui Zhu; Feiyue Wang; Dong Zhen; Huibo Zhang (Jixie chuandong)
Planetary gearboxes are widely used in mechanical transmission systems due to their large transmission ratio and high transmission efficiency. In a planetary gearbox， the sun gear is usually set to float to balance the sharing of loads among planet gears. However， this floating set will result in the variation of pressure angle， overlap ratio and meshing phase in the meshing progress. In the previous studies， these parameters were reduced to constant. To study the influence of the dynamic parameters on the vibration response of planetary gearboxes under different operating conditions， a new lumped parameter model containing the time-varying pressure angle， time-varying overlap ratio and time-varying meshing phase is established. Based on this model， the vibration response mechanism of the sun gear is analyzed. Moreover， the comparison with the previous model is made and the rule of phase modulation caused by these dynamic parameters is revealed. By comparing the dynamic responses under different loads and rotation speeds， the phase modulation is studied in detail.